Mitigation potential of green structures on local urban microclimate using ENVI-met model. Issue 3 (2nd September 2017) - Ebrahimnejad, Ramin; Noori, Omid; Deihimfard, Reza
ABSTRACT: Establishing green roofs has been used as a method to mitigate urban environmental quality problems. In this study, the effect of Tehran Nature Bridge green roof as a sustainable structure on its surrounding microclimate is investigated using urban microclimate model, ENVI-met, on a hot summer day in July 2015. For this purpose, two simulation scenarios were generated to assess the impact of extensive and intensive green roofs on some climate variables. A comparison was made between the scenarios at two different heights, 1.5 and 40.5 m and two times including 10 am and 4 pm. Based on the predicted results, the second scenario showed a 10.47% increase in relative humidity (RH) compared to the first scenario on bridge level at 10 am. In the second scenario, air temperature dropped by 0.8°C at 10 am compared with the first scenario, which is equivalent to 2.87%. The presence of intensive green roof caused a decrease in wind velocity on bridge level by 1.75 m/s and changed its direction. Furthermore, green roof also influenced velocity and direction of the wind, RH, and air temperature in different ways at ground level. Overall, green roof altered climatic parameters such as air temperature, RH, and wind velocity and direction at both bridge and ground level.